Oligo targeting for profiling drug resistance mutations in the parasitic trypanosomatids. Issue 14 (7th May 2022) - Altmann, Simone; Rico, Eva; Carvalho, Sandra; Ridgway, Melanie; Trenaman, Anna; Donnelly, Hannah; Tinti, Michele; Wyllie, Susan; Horn, David
Abstract: Trypanosomatids cause the neglected tropical diseases, sleeping sickness, Chagas disease and the leishmaniases. Studies on these lethal parasites would be further facilitated by new and improved genetic technologies. Scalable precision editing methods, for example, could be used to improve our understanding of potential mutations associated with drug resistance, a current priority given that several new anti-trypanosomal drugs, with known targets, are currently in clinical development. We report the development of a simple oligo targeting method for rapid and precise editing of priority drug targets in otherwise wild type trypanosomatids. In Trypanosoma brucei, approx. 50-b single-stranded oligodeoxynucleotides were optimal, multiple base edits could be incorporated, and editing efficiency was substantially increased when mismatch repair was suppressed. Resistance-associated edits were introduced in T. brucei cyclin dependent kinase 12 (CRK12, L 482 F) or cleavage and polyadenylation specificity factor 3 (N 232 H), in the Trypanosoma cruzi proteasome β5 subunit (G 208 S), or in Leishmania donovani CRK12 (G 572 D). We further implemented oligo targeting for site saturation mutagenesis, targeting codon G 492 in T. brucei CRK12. This approach, combined with amplicon sequencing for codon variant scoring, revealed fourteen resistance conferring G 492 edits encoding six distinct amino acids. The outputs confirm on-target drug activity, reveal a variety of resistance-associated mutations, and facilitate rapid assessment of potential impacts on drug efficacy.